Elevated 4R‐tau in astrocytes from asymptomatic carriers of the MAPT 10+16 intronic mutation. Issue 4 (24th December 2021) - Setó‐Salvia, Núria; Esteras, Noemi; de Silva, Rohan; de Pablo‐Fernandez, Eduardo; Arber, Charles; Toomey, Christina E.; Polke, James M.; Morris, Huw R.; Rohrer, Jonathan D.; Abramov, Andrey Y.; Patani, Rickie; Wray, Selina; et al.
Abstract: The microtubule‐associated protein tau gene ( MAPT) 10+16 intronic mutation causes frontotemporal lobar degeneration (FTLD) by increasing expression of four‐repeat (4R)‐tau isoforms. We investigated the potential role for astrocytes in the pathogenesis of FTLD by studying the expression of 4R‐tau. We derived astrocytes and neurons from induced pluripotent stem cells from two asymptomatic 10+16 carriers which, compared to controls, showed persistently increased 4R:3R‐tau transcript and protein ratios in both cell types. However, beyond 300 days culture, 10+16 neurons showed less marked increase of this 4R:3R‐tau transcript ratio compared to astrocytes. Interestingly, throughout maturation, both 10+16 carriers consistently displayed different 4R:3R‐tau transcript and protein ratios. These elevated levels of 4R‐tau in astrocytes implicate glial cells in the pathogenic process and also suggests a cell‐type‐specific regulation and may inform and help on treatment of pre‐clinical tauopathies.